Object Serialization Formats and Techniques a Review (Global Journal of Computer Science and Technology, 2013)
Serialization is a process of converting an object into a stream of data so that it can be easily transmittable over the network or can be continued in a persistent storage location. This storage location can be a physical file, database or Network Stream. This paper concludes some the work that is going on in the field of Object Serialization. This paper presents Object Serialization Techniques that can be useful for various purposes, including object serialization Minimization which can be used to decrease the size of Serialized data.
Keywords: object serialization; compression techniques; object oriented design; performance analytics; soap